Trafficking in human beings in Spain: What do the data on detected victims tell us? - Villacampa, Carolina (European journal of criminology, 2023)
Although trafficking in human beings was criminalized in Spain in 2010, data on this phenomenon are scarce and incomplete, consisting only of cases formally identified by police as having a very clear bias to trafficking for sexual exploitation. In an effort to increase empirical understanding, in 2019 we undertook quantitative research by gathering information on cases detected during 2017 and 2018. A questionnaire was distributed online to 757 stakeholders who could potentially have come across victims of trafficking. The 150 responses obtained provide valuable information about the number of victims, their profile, the dynamics of trafficking and the types of exploitation they suffered. The number of victims detected during the research period (n?=?7448) is far higher than those officially identified (n?=?458), which indicates that official cases may represent only the tip of the iceberg and point to the necessity of adopting measures to improve the identification system. Findings also show differences in victims? profiles, victimization dynamics and forms of exploitation depending on the type of trafficking that could be taken into account when designing intervention and prevention programmes in this matter.